Improving Exoskeleton Functionality: Design and Comparative Evaluation of Control Techniques for Pneumatic Artificial Muscle Actuators in Lower Limb Rehabilitation and Work Tasks - Urrea-Onate, E; Agramonte-Alburquerque, R (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
The study of lower limbs has become relevant in recent years. Lower limbs have several classifications, but the most widespread categories are robots for patient rehabilitation and robots for work tasks. Two of the main pillars in the development of exoskeletons are actuators and control strategies. Pneumatic artificial muscles are similar to human muscles in their function. This work focuses on this similarity to develop control techniques for this type of actuator. The purpose of this investigation is to design, evaluate, and compare the effectiveness of three different control systems—the proportional–integrative–derivative (PID) system, the sliding mode control (SMC) system, and the fuzzy logic controller (FLC) system—in executing precise trajectory tracking using an exoskeleton and including very realistic dynamic considerations. This study aims to design and implement these controllers and assess their performance in following three distinct trajectories, thereby determining the most efficient and reliable control method for exoskeleton motion. Additionally, the analysis centers on both the response of the controllers to external perturbations and the reaction of the controllers when the time delay inherent to their dynamic is added to the mathematical model. Finally, the results are compared, revealing through the analysis of performance indexes and time response that the FLC is the controller that exhibits the best global results in the tracking of the different trajectories. This work demonstrates that, for the system in question, the action of adding a time delay in the actuator causes the FLC and PID controllers to maintain a similar response, which is obtained without the delay action, in contrast to the system with an SMC controller. However, the same does not occur when including other dynamic factors, such as disturbances external to the system. © 2023 by the authors.